MORPHOLOGICAL CHARECTERIZATION OF KENAF (H ibiscus cannabinus L.) I N MALAYSIAN TROPICAL ENVIRONMENT USING MULTIVARIATE ANALYSIS - G. Faruq; M. A. Alamgir; M. M. Rahman; M. R. Motior; H. P. Zakaria; B. Marchalina; N. A. Mohamed (Journal of Animal and Plant Sciences, 2013)
Kenaf (Hibiscus cannabinus L.) is a green resource of natural fibre. But our understanding of genotypic characteristics and relationships between kenaf genotypes grown up in certain environmental condition is limited, which is important for effective kenaf breeding program for mass commercial production and fundamental need for utilization of this resource. Thirty two kenaf genotypes originated from different parts of the world were cultivated in open field of Malaysian tropical environment. A total of 15 morphological data were collected and multivariate analysis was used to identify the genetic variation among the genotypes. There were significant differences among the genotypes in fibre weight, days to 50% flowering and days to maturity. Principal component analysis showed that days to flowering, days to maturity, plant diameter and leaf shape were the traits responsible for major variation among the genotypes. In cluster analysis different kenaf genotypes produce three distinct groups which can be used for selection of parents of in the breeding program. From total three clusters, high yielding late mature genotypes of the cluster 3 can be used to cross with middle flowering genotypes of cluster 2 to produce relatively photo insensitive variety with better fibre and stick yield in Malaysian tropical environment.
Keywords: Kenaf; Characterization; Genotype; Cluster analysis; Principal Component Analysis